Karakteristik Papan Komposit dengan Substitusi Tandan Kosong Kelapa Sawit (TKKS) dan Perlakuan Susunan Serat - Alwi Mashudin Yahya; Ida Bagus Banyuro Partha; Reni Astuti Widyowanti (BIOFOODTECH : Journal of Bioenergy and Food Technology, 2025)
Composite boards are generally made from plastic and natural wood, on the one hand, oil palm empty fruit bunches (TKKS) which are palm oil mill waste contain lignocellulose which is one of the requirements for composite board making materials. This study aims to determine the effect of TKKS fiber substitution on composite boards, determine the effect of TKKS fiber arrangement on composite boards, determine the composition of TKKS substitution and TKKS fiber arrangement that produces composite boards that are suitable for their uses. This research uses the Complete Block Design (RBL) method with 2 factors. The first factor is the substitution of TKKS based on 20 grams of sengon powder with 3 levels, namely 40% (8 grams), 50% (10 grams), 60% (12 grams). The second factor is the arrangement of the TKKS fibers with 3 levels, namely random, parallel, cross. The results of this study indicate that the substitution of TKKS with sengon powder base affects the chemical properties, namely water content, as well as physical properties in the form of water absorption, thickness development, density, porosity, and flexibility in composite boards. The arrangement of TKKS fibers affects the physical properties which include water absorption, thickness development, density, porosity, and flexibility of the composite board. The best results of this study were found in the treatment of 40% sengon powder: 60% TKKS fiber with an average value of 3,493% moisture content, 27,581% water absorption, 2,241% thick development, 2,13 g/cm3 density, 27,189% porosity, and 63.641 kgf/cm2 flexibility value is the most brittle sample so it is suitable to be applied to furniture such as tables, cabinets, and stacking shelves.